Deaths from asthma in New Zealand. Issue 1 (January 1986) - Sears, M R; Rea, H H; Fenwick, J; Beaglehole, R; Gillies, A J; Holst, P E; O'Donnell, T V; Rothwell, R P; Sutherland, D C
Abstract : We report the first complete population based study of childhood deaths due to asthma. All deaths ascribed to asthma in New Zealand children aged 0-14 were investigated as part of a two year national study of mortality from asthma. The 16 children who died from asthma all developed asthma by the age of 4; 15 had a family history of asthma, and 12 had associated atopic disorders. Disturbed pyschosocial relationships were evident in eight families. Seven children died in less than three hours from the onset of their final attack. All children died outside hospital. Mortality from asthma in Maori children (3.14 per 100 000) was five times that of European children. With hindsight, factors which if avoided could have led to a different outcome were identified in eleven cases. The circumstances surrounding these deaths were similar to those described for adults with asthma; this study, however, underlines the importance of parental care and knowledge in the management of children with asthma. Inadequate long term medical care, underassessment of severity by family and doctors, failure of the family to call for help when required, and inadequate responses of medical services contributed to the fatalities. Excess beta2 sympathomimetic dosage or overreliance on home nebulisers were uncommon. Most childhood deaths from asthma should be prevented by increased family awareness, better assessment of severity, improved long term treatment, and rapid access to emergency medical care.